A label-free fluorescent adenosine triphosphate biosensor via overhanging aptamer-triggered enzyme protection and target recycling amplification. Issue 13 (25th May 2016) - Wang, Zhaoyin; Zhao, Jian; Dai, Zhihui
Abstract : A label-free fluorescent adenosine triphosphate aptasensor is fabricated using an overhanging aptamer that can trigger enzyme protection and target recycling amplification. Abstract : Herein, a label-free fluorescent adenosine triphosphate (ATP) aptasensor is fabricated with a DNA hairpin and an overhanging aptamer. In the presence of ATP, the overhanging sequences of the aptamer may form preferred substrates of exo III, and thus trigger the enzyme-assisted amplification, which results in the release of G-rich sequences. Free G-rich sequences subsequently generate an enhanced flourescent signal by binding with thioflavin T. However, if ATP is absent, the overhanging sequence can induce steric hindrance and protect the DNA hairpin against the digestion of exo III, significantly reducing the noise of this biosensor. Accordingly, the signal-to-noise ratio of the sensing system is greatly improved, which ensures the desirable analytical performance of the proposed aptasensor both in pure samples and real samples.